Effects of power electronics devices on the energy quality of an administrative building - Silva, Jorge I.; Sousa, Vladimir; Sarmiento, Paulo; Gómez, Julio R.; Viego, Percy R.; Quispe, Enrique C. (International Journal of Power Electronics and Drive Systems (IJPEDS), 2019)
This paper proposes the analysis of the effects of power electronics devices on the energy quality of an administrative building. For the study a method is applied that allows the analysis of the main problems of energy quality such as voltage variation, harmonics, flicker, and the effect of harmonics on the power factor. As a case study, the offices of an administrative building were used, where the measurements of the main energy quality parameters were carried out for a week. The results showed the presence of current harmonics and flicker problems due to non-linear loads such as the frequency inverters that drive the motors of the elevators and escalators, as well as the LED lamps. These problems cause systematic damage to the lighting system, UPS and improper correction of the power factor. The study also demonstrates the need to deepen the effects of energy quality not only in the industrial and residential sectors. In addition, attention must be paid to the tertiary sector, specifically to administrative buildings.